Perencanaan Information Technology Service Continuity Management Berdasarkan ITIL V-3 Pada PT Telkom Msc Area V Jawa Timur - Setiawan, Wahyu; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal JSIKA, 2014)
Abstract :Â Telkom MSC (Maintenance Service Center) is one of the divisions of PT. Telekomunikasi Indonesia, Tbk which its major function is to do an infrastructure maintenance management to the telecommunication devices which is owned by Telkom. In order to perform an infrastructure maintenance management, Telkom MSC divides an area of management into seven parts, namely Area I Sumatra, Area II DKI Jakarta, Area III Jawa Barat, Area IV Jawa Tengah dan DIY, Area V Jawa Timur, Area VI Kalimantan and Area VII Kawasan Timur Indonesia (KTI). So far the process of maintenance and repair performed on PT. Telkom MSC Area V Jawa Timur is limited only refers to a standard work that has been set by management, so that there are few activities which could result in an obstacle. Those activities happened not only in the maintenance process but also at the time the repair process is being done. The problems faced by PT. Telkom MSC Area V Jawa Timur are not yet having standards on the process of what to do at the time or before an obstacle occured in the maintenance and repair processes itself, limited only doing a coordination meeting related to the obstacle that is being/has happened in order to make sure it will not happened in the future. Framework ITIL-V3 used as a reference to draw up a pattern of work which is structured. So that by the presence of this standard will give a clear directives work at the time or before an obstacle occured in the maintenance and repair processes, so that the two processes are able to walk on a sustainable basis. And, it could provide improvement recommendations in a form of Standard Operating Procedure (SOP), Instruksi Kerja (IK) and Rekaman Kerja (RK) based on the framework that is concerned with IT Service Continuity Management.